2009
DOI: 10.1101/gad.1837009
|View full text |Cite
|
Sign up to set email alerts
|

An inducible change in Fox-1/A2BP1 splicing modulates the alternative splicing of downstream neuronal target exons

Abstract: Neuronal depolarization and CaM kinase IV signaling alter the splicing of multiple exons in transcripts for ion channels, neurotransmitter receptors, and other synaptic proteins. These splicing changes are mediated in part by special CaM kinase-responsive RNA elements, within or adjacent to exons that are repressed in the initial phase of chronic depolarization. The splicing of many neuronal transcripts is also regulated by members of the Fox (Feminizing gene on X) protein family, and these Fox targets are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(169 citation statements)
references
References 85 publications
8
160
1
Order By: Relevance
“…2A). This result is consistent with previous reports that the C-terminal region is critical for nuclear localization (Nakahata and Kawamoto 2005;Lee et al 2009). …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…2A). This result is consistent with previous reports that the C-terminal region is critical for nuclear localization (Nakahata and Kawamoto 2005;Lee et al 2009). …”
Section: Resultssupporting
confidence: 83%
“…This is consistent with our localization results. It has also been noted that some RBFOX1 isoforms lack the second half of the C-terminal domain because of frame-shifting, and therefore, they are not functional in splicing regulation (Nakahata and Kawamoto 2005;Lee et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have demonstrated that depolarization of neuronal cells induced changes of splicing regulators, which in turn led to alternative splicing changes. [33][34][35][36][37][38] It is possible that the calcium-induced export of class II HDACs changes of post-translational modification of some splicing regulators, e.g., making some proteins more acetylated, which alters their function and then leads to downstream alternative splicing changes. It is very likely that multiple mechanisms exist that control calcium-mediated alternative splicing changes.…”
Section: Discussionmentioning
confidence: 99%
“…P19 cells were differentiated into postmitotic neuronal cells as described previously (50). Briefly, P19 cells were grown in αMEM with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%